EXTRACTION, PURIFICATION AND CHARACTERIZATION OF ELASTASE FROM THE DIGESTIVE DUCT OF CATFISH (SILURUS TRIOSTEGUS) - A. M. Kadhim,; K. A. Shakir, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to extract, purify and characterize the pancreatic elastase from the Catfish (silurus trioseegus) digestive duct. Different extraction solutions were used to optimize the extraction condition being (Distilled water, 200 mM NaCl, Phosphate buffer (100 mM, pH 8), the latter buffer Tis-HCl (100 mM, pH 8) both  containing 0-100 mM NaCl or CaCl2 separately). Tris-HCl buffer containing 100 mM CaCl2 was the best among the rest extraction solutions. The crude extract was precipitated using a 30 % - 55 % of ammonium sulfate saturation ratio. The crude precipitate was dissolved in the same buffer and dialyzed. Then the dialyzed precipitate was concentrated and applied to CM-52 column (3.5 ×10 cm), elastase activity was appeared in two protein peaks. Each peak fraction were pooled individually and loaded on a Sephadex G-75 column (1.6×62 cm). Elastase activity was recovered only from one peak with 29.54 % yield, 530.70 U total activity and 17.89 U/mg specific activity. The optimum temperature for elastase stability and activity was 0-30 C° and 55 C° respectively. while the optimum pH for the enzyme activity and stability were 9 and 4-9 respectively. The molecular weight was 21898 Da as determined by Gel filtration.